Scott Woodbury-Stewart

GMAT OFFICIAL GUIDE PS – In a weight-lifting competition, the total weight of Joe’s…

In a weight-lifting competition, the total weight of Joe’s…

Solution:

This problem is a general word translation. We first define variables and then set up equations.

We can define the following variables:

F = the weight of the first lift

S = the weight of the second lift

We are given that the total weight of Joe’s two lifts was 750 pounds. We sum the two variables to obtain:

F + S = 750

We are also given that twice the weight of his first lift was 300 pounds more than the weight of his second lift. We express this as:

2F = 300 + S

2F – 300 = S

We can now plug in (2F – 300) for S into the first equation, so we have:

F + 2F – 300 = 750

3F = 1,050

F = 350

Answer: D